2016
DOI: 10.1039/c6ra06959b
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional potassium niobate nanoarray on vermiculite for high-performance photocatalyst fabricated by an in situ hydrothermal process

Abstract: Three-dimensional (3D) potassium niobate nanoarray/vermiculite (KNbO 3 /VMT) was synthesized by an in situ hydrothermal method using niobium chloride as the niobium resource. Scanning electron microscopy, high resolution transmission electron microscopy, X-ray diffraction, Fourier transform infrared and X-ray photoelectron spectroscopy tests were used to confirm that KNbO 3 nanoneedles have been grown both on the outer and inner surfaces of natural layered VMT and the growth mechanism of the well-aligned KNbO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Figure a shows the Nb 3 d spectrum of 6N–K 2 Nb 2 O 6 , which could be fitted into four peaks. The two prominent peaks centered at 206.27 and 208.97 eV could be assigned to Nb 5+ , whereas the peak centered at 206.59 and 209.46 eV corresponds to Nb 4+ , [ 41,42 ] confirming the formation of Nb 4+ species in 6N–K 2 Nb 2 O 6 . The N 1 s spectrum of the 6N–K 2 Nb 2 O 6 sample is shown in Figure 3b, which contains three binding energy peaks at 393.4, 395.4, and 401.9 eV.…”
Section: Resultsmentioning
confidence: 92%
“…Figure a shows the Nb 3 d spectrum of 6N–K 2 Nb 2 O 6 , which could be fitted into four peaks. The two prominent peaks centered at 206.27 and 208.97 eV could be assigned to Nb 5+ , whereas the peak centered at 206.59 and 209.46 eV corresponds to Nb 4+ , [ 41,42 ] confirming the formation of Nb 4+ species in 6N–K 2 Nb 2 O 6 . The N 1 s spectrum of the 6N–K 2 Nb 2 O 6 sample is shown in Figure 3b, which contains three binding energy peaks at 393.4, 395.4, and 401.9 eV.…”
Section: Resultsmentioning
confidence: 92%
“…The peak at 659 cm −1 is assigned to the normalONbnormalO stretching vibrations in the corner‐sharing NbO 6 , whereas the peaks at 501 and 817 cm −1 are related to the NbnormalO bonds within the edge‐shared NbO 6 octahedra. Among the couple of Wyckoff orientations, the edge‐shared octahedra are known to exhibit larger structural distortions in reference to the corner‐shared NbO 6 octahedra that strongly apply fluctuations in the NbnormalO bond‐length 33–36 . The peaks at 1707, 2293, and 2390 cm −1 are indicative of axial deformation and normalO=normalC=normalO asymmetric stretching vibrations of the adsorbed CO 2 molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Among the couple of Wyckoff orientations, the edge-shared octahedra are known to exhibit larger structural distortions in reference to the cornershared NbO 6 octahedra that strongly apply fluctuations in the Nb -O bond-length. [33][34][35][36] The peaks at 1707, 2293, and 2390 cm À1 are indicative of axial deformation and O ¼ C ¼ O asymmetric stretching vibrations of the adsorbed CO 2 molecules. Along with CO 2 gas, some amount of moisture is likely chemisorbed in the surface of the nanoparticles.…”
Section: Fourier Transform Infrared Spectrum (Ftir): Vibrational Prop...mentioning
confidence: 99%
“…[127] Hydrogen evolution from aqueous formic acid [143] KNbO3 has been similarly explored for its photocatalytic activity. [131][132]136] Wang et al used vermiculite as a substrate on which to grow KNbO3 needles that showed photoactivity for degradation of methyl blue, [134] while nitrogen-doping of KNbO3 prepared hydrothermally was possible by heat treatment in the presence of urea to tune photocatalytic properties. [144] Using ethanol as solvent and NbCl5 as precursor, Nb 4+containing KNbO3 was prepared with improved water splitting properties; these could also be readily nitrided in a second step with ammonia to give a surface modified with Nb4N5 that showed enhanced photocatalysis properties, ascribed to the introduction of some Nb 4+ , and the junction between the oxide and nitride.…”
Section: Niobates and Tantalatesmentioning
confidence: 99%